Development of student worksheets with contextual teaching and learning (CTL) approach to train critical thinking skills responsibility of students on thermochemistry concepts - Sitti Kholifah Amartyah; Rusmini Rusmini (Jurnal Pijar Mipa, 2022)
This study aims to produce and describe the feasibility of student worksheets with a contextual teaching and learning CTL approach in training critical thinking skills and responsibility in thermochemical material. This study uses a research and development type, the ADDIE (Analysis, Design, Development, Implementation, Evaluation). The research sample was 24 students of class XI IPA MA Nurut Taqwa Grujugan Cermee Bondowoso, West Java, Indonesia. The results showed that: 1) Validity analysis obtained an average percentage of 87% with very valid criteria; 2) Practical analysis based on the percentage of response questionnaires and student activity observations of 88% and 98% with very practical criteria; 3) Analysis of effectiveness based on pretest-posttest data: a) Normality test of cognitive knowledge and critical thinking skills 0.985 and 0.297 normally distributed; b) Paired Sample t-Test 0.000 showed an increase in learning outcomes; c) The N-Gain test of cognitive knowledge and critical thinking skills scored 78% and 76% showed an increase in learning outcomes and attitude of respondents obtained a score of 87% with very good criteria. IN conclusion, the developed student worksheet with the CTL approach is categorized as feasible with valid, practical, and effective criteria. The development of student worksheets as teaching material to improve students' critical thinking skills becomes a choice for learning to make learning more meaningful, accompanied by the attitude of students who are full of responsibility, which is an important thing to do.